Are ambient volatile organic compounds environmental stressors for heart failure?. (November 2018) - Ran, Jinjun; Qiu, Hong; Sun, Shengzhi; Yang, Aimin; Tian, Linwei
Abstract: Background: Numerous epidemiological studies have indicated the adverse cardiovascular effects of air pollution on heart failure (HF) risk. However, little data are available directly evaluating the association of ambient volatile organic compounds (VOCs) with HF risk. We aimed to estimate the short-term effects of ambient VOCs on HF emergency hospitalizations in Hong Kong and to evaluate whether the associations were modified by sex and age. Methods: We collected the daily VOCs concentrations from the Hong Kong Environmental Protection Department between April 2011 to December 2014. HF emergency hospital admission data were obtained from the Hospital Authority of Hong Kong. Generalized additive model (GAM) integrated with the distributed lag model (DLM) was used to estimate the excess risks of HF emergency hospitalizations with ambient concentrations of each VOCs groups – alkane, alkene, alkyne, benzene and substituted benzene. Results: We observed short-term effects of alkyne and benzene on an increased risk of HF emergency hospitalizations. The cumulative effect over 0–6 lag days (dlm0-6 ) for an IQR increment of alkyne (1.17 ppb) was associated with 4.2% (95% CI: 1.18%–7.26%) increases of HF emergency hospitalizations, while the corresponding effect estimate over dlm0-2 for benzene per IQR (0.43 ppb) was 2.7% (95% CI: 0.39%–5.04%). Each VOCs groups was significantly associated with HF emergency hospitalizations in men. Conclusions: Ambient volatile organic compounds, particularly alkyne and benzene, were associated with increased risks of heart failure in the Hong Kong population. Graphical abstract: Image 1 Highlights: Evidence on health effects of ambient VOCs on heart failure is insufficient. Generalized additive distributed lag model were used to estimate effects of VOCs. We observed short-term effects of alkyne and benzene on HF hospitalizations. Health impacts of VOCs on HF were stronger in men.